Fully doped chromium-vanadium cast irons for production of high wear-resistant parts - S. S. Gurin; Yu. A. Saunin (Литьë и металлургия)
The influence of complex doping on the structure formation and characteristics of chromium-vanadium cast iron is considered. Influence of the quantity of carbides in the structure of cast iron on its wear resistance is marked.